Sistem Pendukung Keputusan Penentuan Kelas Tunagrahita Menggunakan Metode Weight Product - Rizky, Robby; Hakim, Zaenal; Susilawati, Susilawati; Setiowati, Sri; Yunita, Ayu Mira; Wardah, Neli Nailul; Sugiarto, Agung; Pratama, Aghy Gilar; Hakim, Moh Azizi; Wibowo, Andrianto Heri; Heriyana, Erik; Sukmara, Sony; Prianggita, Veny Agustini (Jurnal Teknik Informatika UNIKA Santo Thomas, 2023)
The core problem in this study is the difficulty of determining classes for mentally retarded children. Mentally retarded children are children with special needs that must be considered in terms of education, to assist in the teaching and learning process for mentally retarded children, a very good class grouping is needed to support the teaching and learning process. The purpose of this study is to build a decision system that can determine and classify classes for mentally retarded children. The method used in this study is the Wight Product method by determining a criterion that exists in this study. The results of this study are a system that can determine classes for special needs that can assist in the learning process with mental retardation needs.